The Effects of Technology Abuse to Social Life as Reflected in Mary Shelley's Frankenstein - Muhammad Ardiansah; Burhanuddin Arafah; Herawaty Abbas (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This study aims to describe and to elaborate the form of technological abuse effects to social life as reflected in Shelley’s Frankenstein. The researcher used a sociology literature approach to find out the forms of technological abuse effects to social life as reflected in the novel. The primary data were taken from Frankenstein's novel and the secondary data were taken from library search including articles and journals. The researcher used note-taking in collecting data. The result of this research found two forms of technological abuse effects to social life that are illustrated in the novel, namely: Anti-Social and Procrastination.